Dictionary on comprehensive security in Indonesia. Acronyms and Abbreviations. Kamus Keamanan komprehensive Indonesia. Akronim dan Singkatan - Wandelt, Ingo (Friedrich Ebert Stiftung, 2009)
Dictionary on comprehensive security in Indonesia. Acronyms and Abbreviations ....